Health and safety in refurbishment projects involving demolition work - Rakhshanifar, Mansooreh (2013)
Refurbishment is any upgrade, alteration, modification in the current status of the building to improve performance and efficiency of the structure. Refurbishment projects involve structural alteration, retention and partial demolition which merely coincide with different risks. The importance of considering safety issues and developing management strategies applicable for refurbishment practice arise as a result of increase in the total number of the refurbishment projects and growth of the fatality rate caused by refurbishment work. Increase in the number of accidents may affect project team in many aspects. Financial losses and delay in the completion of work are the typical consequences caused by refurbishment activities. On the critical cases, the public image of the contractors, clients, and management team as general, will be damaged. Therefore, providing a safety and health check list may assist to reduce incompliance with health and safety regulations and to improve communication flow in refurbishment projects. Further, this check list may be used as a basis for the health and safety trainings for the workers. To achieve this target, demolition techniques, methods and accident reports on the refurbishment project has been identified and reviewed. Next, a semi-structured interviewed was conducted to provide a list of common hazards occurring in the site and appropriate precautions that can be applied in the project to prevent accidents in working place. The obtained result was organized in a check list of activities, preventive actions and recommendations.